The role of footwear in improving running economy: a systematic review with meta-analysis of controlled trials - Liya Xu; Yifan Wang; Xu Wen (Scientific Reports)
Abstract This systematic review aimed to explore the impact of different types of footwear and footwear characteristics on the running economy (RE) of long-distance runners and providing guidance for running enthusiasts and clinical practice. A comprehensive search of Web of Science, PubMed, SPORTDiscous, SCOPUS, and the China National Knowledge Infrastructure (CNKI) databases from inception to April 2024 was performed. Trials evaluating the RE of adults participating in long-distance running included comparing different footwear characteristics. This review followed the PRISMA statement. Two reviewers screened titles and abstracts to make a relevant shortlist, then retrieved and evaluated full texts against inclusion criteria for eligibility. Two independent reviewers evaluated the methodological quality of each included analysis by employing the Physiotherapy Evidence Database Scale (PEDro scale). The standardized mean difference (SMD) for the results of RE studies in each study was calculated. Of the 1338 records retrieved, 26 studies were identified in the systematic review and meta-analysis. Limited evidence indicated that compared with shod running, barefoot running (SMD = − 0.50 [95% CI − 0.86, − 0.14], P = 0.006) and minimalist running (SMD = − 0.62 [95% CI − 0.83, − 0.42], P < 0.00001) had a positive impact on RE. Compared with barefoot running, minimalist running did not show a beneficial effect (SMD = 0.37 [95% CI − 0.07, 0.81], P = 0.10) on RE. Additionally, compared with the control condition, RE showed some improvement with increased footwear longitudinal bending stiffness (SMD = − 0.53 [95% CI − 0.90, − 0.17], P = 0.005) and cushioning (SMD = − 0.33 [95% CI − 0.61, 0.06], P = 0.02). However, compared with control, RE did not change with footwear comfort (SMD = − 0.11 [95% CI − 0.42, 0.21], P = 0.51). Barefoot running or minimalist running may be more economical than shod running, high longitudinal bending stiffness and high cushioning shoes could improve RE.